Advances in web-based learning - ICWL 2014 : 13th International Conference, Tallinn, Estonia, August 14-17, 2014. Proceedings - Lau, Rynson W. H.; Pata, Kai; Leung, Howard; Laanpere, Mart; Popescu, Elvira (Lecture Notes in Computer Science, 2014)
This book constitutes the refereed proceedings of the 13th International Conference on Web-Based Learning, ICWL 2014, held in Tallinn, Estonia, in August 2014. The 18 revised full papers presented together with 9 short papers were carefully reviewed and selected from about 78 submissions. The papers are organized in topical sections on computer supported collaborative learning, Web 2.0 and social learning environments; personal learning environments; game-based learning; learner modeling and learning analytics; personalized and adaptive learning; design, model and implementation of e-learning platforms and tools; and pedagogical issues, practice and experience sharing.